Analysis of Load Characteristics Changes in the Case of Large-scale Electric Energy Substitution Load Connected-in. Issue 4 (February 2020) - Li, Zhuonan; Liu, Jun; Jin, Yanming
Abstract: Global energy development trends and resource endowments determine that clean substitution and electric energy substitution will be important directions for the sustainable development of world energy. Electricity has the advantages of cleanness, safety, and convenience. The implementation of electric energy substitution is of great significance to promote the energy consumption revolution, implement the national energy strategy, and promote clean energy development. At present, many provincial and municipal governments are committed to promoting electrical energy substitution to complete the energy revolution on the consumer side, which has put the local power system to the test. In this paper, a load characteristic change model based on artificial bee colony algorithm for large-scale access of electric energy substitution load is established. In addition, the power load in a typical area is used as an example, and its load change is also calculated.